Molecular mechanism of the spider toxin κ-LhTx-I acting on the bacterial voltage-gated sodium channel NaChBac - Xiao, Zhen; Li, Yaqi; Zhao, Piao; Wu, Xiangyue; Luo, Guoqing; Peng, Shuijiao; Liu, Hongrong; Tang, Cheng; Liu, Zhonghua (Frontiers in Pharmacology, 2022)
The bacterial sodium channel NaChBac is the prokaryotic prototype for the eukaryotic NaV and CaV channels, which could be used as a relatively simple model to study their structure–function relationships. However, few modulators of NaChBac have been reported thus far, and the pharmacology of NaChBac remains to be investigated. In the present study, we show that the spider toxin κ-LhTx-1, an antagonist of the KV4 family potassium channels, potently inhibits NaChBac with an IC50 of 491.0 ± 61.7 nM. Kinetics analysis revealed that κ-LhTx-1 inhibits NaChBac by impeding the voltage-sensor activation. Site-directed mutagenesis confirmed that phenylalanine-103 (F103) in the S3–S4 extracellular loop of NaChBac was critical for interacting with κ-LhTx-1. Molecular docking predicts the binding interface between κ-LhTx-1 and NaChBac and highlights a dominant hydrophobic interaction between W27 in κ-LhTx-1 and F103 in NaChBac that stabilizes the interface. In contrast, κ-LhTx-1 showed weak activity on the mammalian NaV channels, with 10 µM toxin slightly inhibiting the peak currents of NaV1.2–1.9 subtypes. Taken together, our study shows that κ-LhTx-1 inhibits the bacterial sodium channel, NaChBac, using a voltage-sensor trapping mechanism similar to mammalian NaV site 4 toxins. κ-LhTx-1 could be used as a ligand to study the toxin–channel interactions in the native membrane environments, given that the NaChBac structure was successfully resolved in a nanodisc.